Lesson in red : a novel - Hummel, Maria (Counterpoint, 2021)
"Brenae Brazil is a rising star at Los Angeles Art College, the most prestigious art school in the country, and a pupil of the institution's equally famous and influential director, Hal Giroux. Brenae's path to art world stardom is all but assured, so why did she kill herself shortly after completing a provocative documentary about female bodies, violence, and self-defence? Maggie Richter's return to LA and her old job at the Rocque Museum was supposed to be about restarting her career, reconnecting with old friends, and maybe starting to date again. The last thing she expected was to find herself at the center of another art world mystery concerning the death of Brenae Brazil. Are there hidden clues in Brazil's other works of video art? Maggie will get pulled into the cryptic video art of Brazil that will send her down the rabbit hole of art schools, power struggles over students and mentors, and the still shady and often violent art world in Los Angeles. The work of Kim Lord and the fallout of the Still Lives exhibition looms continually over Maggie and our other returning cast members. Picking up where Still Lives-a Reeses's Book Club and Hello Sunshine selection-left off, Lesson In Red is a fast-paced thriller set against the cutthroat world of high art and the often fatal legacies of women who threaten its status quo"--